(untitled) (TAJ: Journal of Teachers Association, 2020)
Introduction: Dental caries is one of the most common oral health diseases among children all over the world and its consequences cause a lot of pain and suffering. In the present study the effect of cariogenic food and socio-economic status in the initiation of dental caries among pediatric patients was assessed. Methodology: Data were collected with a pretested structured interview schedule from 370 participants and their parents attending dental unit, Rajshahi medical college from July 2017 to December 2018. Oral examination was done by dental mirror and probe under sufficient light to find out the dental caries among the children. Data were analyzed using SPSS method. Results: 91.35% participants had dental caries. Multiple caries was found highest (56. 58%) in low socio-economic status. 68.38% participants regularly consumed the cariogenic food, of them multiple caries were found in 46.64%. Discussion: The prevalence of dental caries among participants was found 91.35%. In the present study family income has influence on the dental caries. In the present study 68.38% participants regularly consumed sugar containing food items and among them multiple carious teeth were found in 46.64% participants. Conclusion: Incidence of dental caries is very high among the children of low socio-economic status and who take cariogenic food frequently specially sugar containing food. TAJ 2019; 32(2): 43-47